2018
DOI: 10.1101/243857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maximum entropy models reveal the correlation structure in cortical neural activity during wakefulness and sleep

Abstract: Maximum Entropy models can be inferred from large data-sets to uncover how local interactions generate collective dynamics. Here, we employ such models to investigate the characteristics of neurons recorded by multielectrode arrays in the cortex of human and monkey throughout states of wakefulness and sleep. Taking advantage of the separation of excitatory and inhibitory types, we construct a model including this distinction. By comparing the performances of Maximum Entropy models at predicting neural activity… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A major challenge is also to account for the diversity of stimuli or even of neural states present in the recordings, and recapitulate this diversity in a single model. It is still challenging for a model to account for both awake animals and slowwave sleep, as neurons behave differently in these regimes (Nghiem et al, 2018). Coarse-grained, modular models such as the hierarchical model (Santos et al, 2010), with different types of interactions at different spatial scales, offer promising avenues for this feat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major challenge is also to account for the diversity of stimuli or even of neural states present in the recordings, and recapitulate this diversity in a single model. It is still challenging for a model to account for both awake animals and slowwave sleep, as neurons behave differently in these regimes (Nghiem et al, 2018). Coarse-grained, modular models such as the hierarchical model (Santos et al, 2010), with different types of interactions at different spatial scales, offer promising avenues for this feat.…”
Section: Discussionmentioning
confidence: 99%
“…In the salamander retina (Gardella et al, 2016), the population activity explained 50% of pairwise correlations, which was similar to what was reported in mouse V1 . Recent application of the population coupling model to the human and monkey cortices showed that the model explained the collective activity well during sleep, but that detailed interactions between specific pairs of neurons mattered during wakefulness (Nghiem et al, 2018). SImilarly, in mouse V1, population rate predicted better pairwise correlations during synchronized states, and very little during desynchronize states .…”
Section: Models Of Population Couplingmentioning
confidence: 99%
“…In recent years, the field of statistical inference applied to neuronal dynamics has mainly focused on devising models and procedures that could reliably recover the real or effective synaptic structure of a network of neurons, under different dynamical and stimulation conditions 3,30,31 , even though, more often than not, an experimental ground truth was not readily available.…”
Section: /13mentioning
confidence: 99%
“…Entropy maximization or related concepts has been frequently utilized in the past ten years to analyze large biological datasets in various fields. These fields range from determining macromolecular interactions and structures [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] to inferring signaling [ 21 , 22 , 23 , 24 , 25 ] and regulatory networks [ 26 , 27 , 28 ] and the coding organization in neural populations [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] based on DNA sequence analyzes (the detection of specific binding sites, for instance) [ 42 , 43 , 44 , 45 , 46 ]. MEM is a powerful vehicle to reconstruct images based on various datasets.…”
Section: Introductionmentioning
confidence: 99%